Investigation of shear piezoelectric fiber composite for flexible sensor application. (8th November 2019) - Yan, Mingyang; Yuan, Xi; Zhang, Yan; Zhang, Shaofeng; Wang, Xiaoyu; Gao, Feng; Zhou, Kechao; Zhang, Dou
Abstract: In this paper, we demonstrate the availability of flexible shear piezoelectric fiber composite (SPFC) to sense the acceleration, shear stress and light levels of excitation. Two kinds of cantilever beam structures based on SPFC were employed to demonstrate the sensing performance. The sensor with sandwiched beam structure exhibits better sensitivity to the acceleration. In the three point bending test, the sensor shows the ability to detect the shear stress. Also, it was proved that the sensor was able to sense light levels of excitation. This work provides a potential application of the shear piezoelectric sensor to detect shear stress failure in structural health monitoring.